An Overview of Selected Yusof Ghani Abstract Expressionist Painting - Mat Isa, Mohd Jamil; DuruIaman, Zaim (Environment-Behaviour Proceedings Journal, 2023)
This review analyzes Yusof Ghani’s painting, which is recognized with the abstract expressionist character. The selected painting was chosen from the private’s collection, then captured into a digital mode which will assist in the analysis of the content and context of the painting. This artwork appears to be very successful in its presentation. This study clearly shows the appropriate features of abstract expressionist style applied by the artist in his painting. The selected painting, through the analysis, depicts the exploration of movement that was attached to the technique, which is associated with the style and contexts.